Comparative Effects of Freeze-Drying and Spray-Drying on the Physicochemical, Microbiological, and Sensory Properties of Coconut Milk and Dairy Milk Yoghurts (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
Coconut milk yoghurt, rich in healthy fats, offers a sustainable alternative to dairy. Converting it into powder enhances shelf life, versatility, and probiotic retention for diverse food applications. This study evaluates the effects of spray-drying (SD) and freeze-drying (FD) on the physicochemical, microbiological, and sensory properties of coconut milk-based yoghurt (CMY) compared to dairy yoghurt (DY). Yoghurt powders were prepared by diluting the yoghurts with 64% distilled water and 6% maltodextrin for SD processing, conducted at 150°C inlet and 65–70°C outlet temperatures. For FD, liquid yoghurts were frozen overnight and lyophilized under vacuum at -50°C for four days.  Analysis revealed that dried CMY exhibited significantly higher soluble solids and lactic acid levels than dried DY (
Keywords: Coconut-based yoghurt; Probiotic viability; Functional food; Lactic acid bacteria; Spray and Freeze dryin